INTEGRATED STOCHASTIC MODELING OF PETROPHYSICAL PARAMETERS FOR THE ESTIMATION OF MINERALOGICAL COMPOSITION OF THE EARTH CRUST - Virshylo, I.; Pap, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The construction of a new algorithm for spatial modeling of the composition of rocks, which is consistent with the results of geophysical, petrophysical and geochemical studies, is considered. The probability distributions of the quantities simulated – volume concentrations of rockforming minerals and voids and the parameters of the thermally stressed state of the medium – pressure and temperature are used as input parameters of the model. The determination of probability distributions is carried out by statistical processing of the results of geological and geochemical studies for the composition and the introduction of confidence intervals for the results of geophysical studies. The method of conditional moment functions for the problem of seismic acoustics, thermometry, magnetometry and electrometry is used as calculation algorithms. The algorithm is based on a multicomponent matrix model of a medium with ellipsoidal inclusions and has no restrictions on the concentration of components. The algorithm makes it possible to take into account arbitrary symmetry of the medium. The result of the simulation is a statistically significant set of decisions that have a geological meaning and are limited to the probability distribution of the concentrations of rock-forming minerals.
Keywords: deep seismic sounding; seismic and mineralogical models; global optimization methods; stochastic methods; direct problem of seismic acoustics; Monte Carlo method; method of conditional moment functions